REDESIGN UI/UX APLIKASI SH-UPI MENGGUNAKAN KERANGKA KERJA DESIGN THINKING - Nissa Restyasari; Syifaul Fuada; Endah Setyowati (Program Studi Pendidikan Informatika, Universitas Citra Bangsa, 2023)
Nowadays, Smart Home technology has been widely reached by society and utilized by most people, from the upper to the middle class, with various brands and products including its features. Smart Home Universitas Pendidikan Indonesia (SH-UPI) is a commercial smart home platform, a new player in this technology business. UPI Academics developed the SH-UPI platform; they successfully commercialized a smart LED Bulb (RGB lamp). The product is managed by a particular Android application, i.e., SH-UPI Apps; it can be downloaded on the Play Store or the official website. However, based on information from the developer, this application has yet to consider good UI/UX aspects during production. Therefore, it is highly necessary to redesign the SH-UPI application to give users a more comfortable (user-friendly) and is competitive against other competitors. The SH-UPI Apps was redesigned using the Design Thinking framework. This method comprises five stages: Empathize, Define, Ideate, Prototype, and Test. This preliminary study focuses on the Empathize, Define, Ideate, and Prototype stages. The results reveal that the Emphatize stage has been carried out well, which concludes that the application needs to be redesigned to improve the user experience’s quality. A mock-up for the new SH-UPI Apps version has been introduced in the Define to Ideate stages. The results of this study can be used as a reference for developing SH-UPI Apps with much better UI/UX. Afterward, the study will continue to further stages: Test.